Inovasi Berkelanjutan: ESG Initiatives Untuk Masa Depan Yang Bertanggung Jawab - Hendro, Junaidi; Bowo Pranogyo, Antaiwan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2023)
In an era of globalization marked by rapid technological progress, sustainability has become a central issue governing many aspects of human life. Sustainability is no longer just an academic term but a guiding principle that guides action and innovation across all sectors. Continuous innovation plays an important role in responding to environmental, social and corporate challenges in operating responsibly. ESG (Environmental, Social and Governance) principles have emerged as a key framework inspiring continuous innovation, key to creating a more sustainable and responsible future. In the context of the port industry, Pelindo, one of the largest operators, is committed to various ESG initiatives to maintain sustainability in its operations. These measures include environmental, social and governance actions aimed at reducing environmental impact, improving the well-being of communities surrounding the port and strengthening corporate governance. Pelindo understands the importance of maintaining ecosystems and creating a positive impact. This effort, therefore, constitutes an important step towards a socially and environmentally responsible future. Close collaboration between government, business and communities is needed to promote sustainability in the port industry, considering sustainable logistics practices and low-carbon energy as solutions for a more sustainable future.